13. Online Videoconferencing Products - Craven, Pam; Keppy, Brian; Baggaley, Jon (International Review of Research in Open and Distributed Learning, 2002)
This is the first in Athabasca University’s series of evaluation reports to feature online Webcam and videoconferencing products. While Webcam software generates a simple visual presentation from a live online camera, videoconferencing products contain a wider range of interactive features serving multi-point interactions between participants. In many online situations, the addition of video images to a live presentation can add substantially to its educational effectiveness. Ten products/ online services are reviewed, supporting a wide range of video-based activities.